2021
DOI: 10.1371/journal.pone.0249917
|View full text |Cite
|
Sign up to set email alerts
|

The association between male involvement in institutional delivery and women’s use of institutional delivery in Debre Tabor town, North West Ethiopia: Community based survey

Abstract: Background Maternal deaths remain high in Ethiopia mainly due to poor maternal health service utilization. Despite men are the chief decision-makers and economically dominant in Ethiopia, the impact of their involvement on maternal health services utilization is not clear. This study aimed to assess the association between male involvement and women’s use of institutional delivery, and factors influencing male partners’ involvement in institutional delivery. Methods A community based cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
3
10
1
Order By: Relevance
“…Concurring with these findings, similar rates were reported in urban and peri-urban parts of east and west Africa including Uganda, (65%) and Nigeria (64%) [33,34]. This study was conducted in urban settings with higher likelihood of male partners' awareness of importance of their involvement in the antenatal care, contrary to situations in peri-urban [35] and rural Tanzania [36], Ghana [8], Ethiopia [12] where prevalence of male involvement was between 18-45%. The observed variation could be explained by the methodological and cultural differences.…”
Section: Prevalence and Determinants Of Male Involvementsupporting
confidence: 77%
See 2 more Smart Citations
“…Concurring with these findings, similar rates were reported in urban and peri-urban parts of east and west Africa including Uganda, (65%) and Nigeria (64%) [33,34]. This study was conducted in urban settings with higher likelihood of male partners' awareness of importance of their involvement in the antenatal care, contrary to situations in peri-urban [35] and rural Tanzania [36], Ghana [8], Ethiopia [12] where prevalence of male involvement was between 18-45%. The observed variation could be explained by the methodological and cultural differences.…”
Section: Prevalence and Determinants Of Male Involvementsupporting
confidence: 77%
“…Data collection was conducted using a structured questionnaire adapted from previous study [28]. The questionnaire covered these topics: a) Demographic parameters such as age, marital status, religion, level of education, occupation, duration of relationship (physical, social or financial) and number of children; b) information on barriers of male involvement in ANC of which women were to choose one or more possible barriers [11,12,29] such as 'being too busy with work', 'thinking its women's' affairs', 'lack of maternal health knowledge' and health service related factors such as 'comfortability to be in antenatal clinic', 'prohibitions to participate during care', 'poorly perceived quality of care', 'staff attitudes', 'inhibitive facility infrastructure' and /or, 'long waiting time'. Questionnaires were screened for completeness and missing information was inquired before data entry, which was concomitantly performed with data collection.…”
Section: Study Population Sampling Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the summative score of variables designed to assess husband involvement with a score equal to or above the mean was considered as involved [15].…”
Section: Husband/partner Involved In Mnch Servicesmentioning
confidence: 99%
“…A systematic review revealed that male involvement is associated with improved maternal health outcomes in developing countries [24]. In African countries, including Ethiopia, male involvement in antenatal care (ANC) and delivery is associated with increased spousal use of skilled birth attendant and postnatal care (PNC) [20,22,[24][25][26]. There are also studies addressing factors influencing male involvement in maternal health services such as ANC, delivery, PNC and family planning [17,18,20,21,23,27], while there is a lack of evidence about male involvement in MWH utilization.…”
Section: Introductionmentioning
confidence: 99%